A realist review of the home care literature and its blind spots. Issue 4 (6th October 2021) - Contandriopoulos, Damien; Stajduhar, Kelli; Sanders, Tanya; Carrier, Annie; Bitschy, Ami; Funk, Laura
Abstract: Rationale, aims and objectives: There is a large body of literature from all over the world that describes, analyzes, or evaluates home care models and interventions. The present article aims to identify the practical lessons that can be gained from a systematic examination of that literature. Method: We conducted a three‐step sequential search process from which 113 documents were selected. That corpus was then narratively analysed according to a realist review approach. Results: A first level of observation is that there are multiple blind spots in the existing literature on home care. The definition and delimitation of what constitutes home care services is generally under‐discussed. In the same way, the composition of the basket of care provided and its fit with the need of recipients is under‐addressed. Finally, the literature relies heavily on RCTs whose practical contribution to decisions or policy is disputable. At a second level, our analysis suggests that three mechanisms (system integration, case management and relational continuity) are core characteristics of home care models' effectiveness. Conclusion: We conclude by providing advice for supporting the design and implementation of stronger home care delivery systems. Our analysis suggests that doing so implies a series of sequential steps: identify what system‐level goals the model should achieve and which populations it should serve; identify what type of services are likely to achieve those goals in order to establish a basket of services; and finally, identify the best ways and specific means to effectively and efficiently provide those services. Those same steps can also support ex‐post evaluations of existing home care systems.